Rural education and pedagogical practice: In schools along the Amazon and Rio Negro rivers during times of conflict and extreme events (Research, Society and Development, 2026)
Rural education needs to be understood from the perspective of its relationship with the community. Observing people's way of life and their relationship with the environment are ways in which society can understand the teaching and learning process in rural areas. Thus, the general objective is to analyze rural education and pedagogical practices in schools along the Amazon and Negro Rivers. Specific objectives include: highlighting the nature of multi-grade classrooms in these schools; demonstrating the importance of developing pedagogical projects in schools along the Amazon and Negro Rivers; and verifying the nature of rural education and pedagogical practices in riverside schools. Methodologically, this is a qualitative field research study. Results were obtained through observations, reports, and semi-structured interviews in four riverside schools with four educators and four school administrators working in multi-grade classes in the first cycle of elementary education. These individuals held distinct conceptions about their pedagogical practices and the evaluation process with students in multi-grade classrooms, which they described as exhausting. Therefore, they seek alternatives and signal to those with the right and responsibility the importance of public policies sensitive to teachers and students, within an administrative and pedagogical organization, encompassing a common school environment for all, with equal teaching and learning rights, specific methodologies for each year/grade, and ensuring that enrollment is done with this teaching-learning perspective and not simply as an adjustment to the Department of Education and Teaching, in a process of disordered staffing.